KONSTRUKSI VERBA GERAKAN DIREKSIONAL BAHASA JAWA : KAJIAN TIPOLOGI* - Agus Subiyanto (Program Magister Linguistik Universitas Udayana, 2010)
Directed motion expressions have two semantic components : path, which carries a directional meaning, and manner of motion. The semantic component of path can be expressed by using a goal preposition phrase (goal PP) or a directional verb. Based on the lexicalization pattern of path, Talmy (1975,1985) classified languages into two types: satellite-framed languages and verb-framed languages. However, Talmy’s typology has raised some controversy because some languages including Javanese use both goal PPs and directional verbs to express path. This paper aims to discuss directed motion constructions in Javanese, and evaluate whether Talmy’s typology is relevant for Javanese. The results of the analysis show that some directional verbs are replaceable with goal PPs but some others have syntactic and semantic patterns different from goal PPs. There is a tendency that Javanese belongs to a verb-framed language since this language does not have adjectival resultatives.